2023
DOI: 10.1002/adma.202209134
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Engineering of Sorption‐Based Atmospheric Water Harvesters

Abstract: Harvesting water from air in sorption‐based devices is a promising solution to decentralized water production, aiming for providing potable water anywhere, anytime. This technology involves a series of coupled processes occurring at distinct length scales, ranging from nanometer to meter and even larger, including water sorption/desorption at the nanoscale, condensation at the mesoscale, device development at the macroscale and water scarcity assessment at the global scale. Comprehensive understanding and besp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 202 publications
0
6
0
Order By: Relevance
“…Freshwater scarcity is increasingly becoming a global problem that affects two-thirds of the global population, with more than half a billion people lacking stable and reliable daily access to clean drinking water . Affordable and energy-efficient freshwater production, especially suitable for providing water in undeveloped and landlocked regions, is urgently needed and has long-lasting significance at both regional and global scales. There are more than 12,900 billion tons of freshwater constantly preserved in the Earth’s atmosphere, known as atmospheric water. , Atmospheric water is increasingly recognized as a promising alternative water resource for freshwater production in water-deficient areas. In recent years, solar-driven sorption-based atmospheric water harvesting (SAWH) technology has been evolving as an attractive means of decentralized drinking water production, especially in areas where a liquid water resource is physically scarce …”
Section: Introductionmentioning
confidence: 99%
“…Freshwater scarcity is increasingly becoming a global problem that affects two-thirds of the global population, with more than half a billion people lacking stable and reliable daily access to clean drinking water . Affordable and energy-efficient freshwater production, especially suitable for providing water in undeveloped and landlocked regions, is urgently needed and has long-lasting significance at both regional and global scales. There are more than 12,900 billion tons of freshwater constantly preserved in the Earth’s atmosphere, known as atmospheric water. , Atmospheric water is increasingly recognized as a promising alternative water resource for freshwater production in water-deficient areas. In recent years, solar-driven sorption-based atmospheric water harvesting (SAWH) technology has been evolving as an attractive means of decentralized drinking water production, especially in areas where a liquid water resource is physically scarce …”
Section: Introductionmentioning
confidence: 99%
“…Chitosan skeleton to be combined with MOFs also endows composites with multifunctionality via electrostatic interaction and hydrogen bonding, 34 e.g., designed as an efficient water evaporator, 35 porous gels, 36 and MOF-based AWH materials. 37,38 Although so, most MOF-based AWH materials show water adsorption at relatively high humidity (e.g., 30−90%), water released under strong light irradiation with high heat (e.g., 50−80 °C), along with low efficiency. 39−41 Up to now, although much research on atmospheric water harvesting has been reported, it is still challenging to develop a robust atmospheric water harvester with ultrahigh uptake-release efficiency at extremely low relative humidity (e.g., RH < 30%).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, as a polymer with cationic polysaccharide, has been developed for water-related applications, , owing to favorable biocompatibility, biodegradability, antibacterial properties, water treatment by complexing and adsorbing pollutants, , and immense potential for AWH. , Abundant functional groups (−NH 2 and −OH) exist on the chitosan chain, which is conducive to form the porous structure as water adsorbent. Chitosan skeleton to be combined with MOFs also endows composites with multifunctionality via electrostatic interaction and hydrogen bonding, e.g., designed as an efficient water evaporator, porous gels, and MOF-based AWH materials. , Although so, most MOF-based AWH materials show water adsorption at relatively high humidity (e.g., 30–90%), water released under strong light irradiation with high heat (e.g., 50–80 °C), along with low efficiency. Up to now, although much research on atmospheric water harvesting has been reported, it is still challenging to develop a robust atmospheric water harvester with ultrahigh uptake-release efficiency at extremely low relative humidity (e.g., RH < 30%).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they hold immense promise in various applications including sorption‐based atmospheric water harvesting, passive humidity and temperature regulation, protective packaging, sustainable agriculture, and energy generation. [ 41–58 ]…”
Section: Introductionmentioning
confidence: 99%